The Evaluation Of English Textbook "Let's Talk" For Junior High School Students Year 9 Based On Rajan's Theory - Akbar, Fadhillah, Aryati Prasetyarini, S.Pd., M.Pd, Drs. Djoko Srijono, M.Hum (2015)
This study focuses on the evaluation of "Let's Talk" English Textbook for Junior High Shool Students year 9 based on Rajan's theory. The objectives of this study are to describe the content of "Let's Talk" English textbook based on Rajan's theory and to describe whether the materials in "Let's Talk" English textbook are good based on Rajan's theory or not. The type of this research is a qualitative research. The object of the study is the content of "Let's Talk" textbook, an Integrated Course of English for Junior High School. The data in this research are the pictures, the expressions, the exercises, the dialogs, the stories, the glossaries, the graphs, and the instructions found in the "Let's Talk" textbook and the data source is the textbook "Let's Talk", an Integrated Course of English for Junior High School published by Pakar Raya. The writer uses documents in collecting data. The data are analyzed by classifying the materials on the textbook based on Rajan's theory, analyzing the collecting data, coding the data, and giving percentage to the materials found in the textbook. The results of the study show 10 good criteria are found based on Rajan's theory. In the in-depth approach, those criteria are motivating (95,08%), meaningful (82,23%), authentic (100%), appropriate (100%), graphic (100%), graded (100%), interesting (50%), interactive (100%), integrated (100%), contextualized (92,92%), and creative (100%). The result of percentage is 92,75%. It means the content of the textbook is good based on Rajan's theory